Design and Fabrication of a Mutual Control Electronic Circuit for Solar and Electrical Water Heating - Al-Talib, Ammar A.; Sarah Atifah, Saruchi; Suhana, Hassan; Nor Aziyatul Izni, Mohd Rosli (The Regents of ALife Robotics Corporation Ltd, 2023)
This research is a temperature controller that will be implemented to ensure that the water temperature of the solar water heating unit is maintained at the desirable level at all times of use. This control circuit is designed to control the On/Off action of the immersed electrical heater according to specific temperature range. A temperature sensor will sense the water temperature constantly and send signal to a micro-controller unit. The micro-controller will process the data according to a written program and control the actions of electrical heater. At the same time, temperature reading will be displayed through LCD and real-time data can be viewed from a computer via serial port. During times of sufficient sunlight, solar energy will be the main source used for heating water; otherwise, there will be an automatic switching to the electrical operated immersion heater. This controller will give reliability to users of solar water heating systems.